People and architecture the role of physical environment in shaping the sense of community in planned and unplanned communities in Davao City - Lalugan, Mac-Clyde a.; Ylagan, Myrafe S. (2018)
The increase in urban population resulted in the increase of housing production. The mass production of housing units to serve the demand resulted in poorly design neighbourhood that does not allow the development of sense of community among residents. The study aims to understand the difference of sense of community between planned and unplanned communities, determine which physical features are significant in influencing the residents' sense of community and examine relationship of physical features and sense of community.Data is collected and analysed using qualitative and quantitative methods from three (3) planned and three (3) unplanned communities in Davao City. Sense of Community Index II was used to measure the sense of community of each study area. Key informant interviews were also conducted to get the first person experience of being a part of the community which was used to further analyse how the physical environment affects sense of community. The results of data collection and analysis was used as a guide in designing a community that fosters the development of sense of community.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2018